Pancasila as a Paradigm of Legal Development in Indonesia - Shelawati Emilia; Mutia Andini; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
- This paper aims to examine the urgency of Pancasila in the development of National Law. Therefore, why Pancasila should be a guide in every law formation in Indonesia. How the philosophical basis of Pancasila is used as a guide in the development of national law and what is the juridical basis. Pancasila is the ideology of the Indonesian nation, the crystallization of the noble values of the Indonesian nation originating from religious values and customary values which are believed to be true and become the basis and guidelines for the behavior of the Indonesian people in the life of the nation and state. Based on this, Pancasila becomes the philosophical basis for the development of national law because the law can be enforced and effective if the law is based on religious values, customary values , and state law. In addition, the basis of the Pancasila state is the source of all sources of law in Indonesia so it becomes a necessity for Pancasila as a philosophical foundation in the development of law in Indonesia. The legal basis for the use of Pancasila as a basic guideline in the development of national law is included in Law Number 10 of 2004 concerning the formation of laws and regulations which was later refined by Law Number 12 of 2011 concerning the formation of laws and regulations. Article 2 of Law Number 12 of 2011 explicitly states that Pancasila is the source of all legal sources. The contents of article 2 contain the understanding that the formation of law must not conflict with the values contained in the precepts of Pancasila.